CONSECUENCIAS DE LA INTERACCIÓN SOCIAL EN LA COMUNICACIÓN INTERCULTURAL DE LA COMUNA CHIGÜILPE, CANTÓN SANTO DOMINGO - Macas Pisco, Freddy Geovanny (2022)
Communication is undoubtedly a beneficial process, since it enriches the levels of knowledge of a person towards others, regardless of the channels used, so it is essential to know all the positive or negative aspects of social interactions, in addition to the communication processes that can be generated in a civilization. At the same time, social interactions facilitate this constant exchange of information, resulting in new paradigms in intercultural societies. For this reason, this research was proposed as an essential objective to establish the consequences of social interaction in intercultural communication in the Chigüilpe commune, in the Santo Domingo canton, it is necessary to mention, in addition to the impact of coexistence, the characteristics of the people who interact in the commune, finally an intercultural communication manual is proposed with the purpose of preserving native customs and traditions of the native Tsáchilas. The investigation was carried out with the level of association of variables because it could constitute predictions through the intervention of the relationships between variables, in addition the degree of relationship between variables was measured and from this, determine trends or models of majority behavior, supports the prospective modality, since it seeks the necessary information to establish the consequences of social interactions in intercultural communication processes, so that obtaining results through the research questionnaire contrasts the information from the observation guide and the interview semi-structured. Thus, the results of the research obtained from the native Tsáchilas showed that social interactions generate favorable economic income, however, in the process they lose their customs and traditions, therefore, it is concluded that the most notable consequence of that is the limited population that currently exists, since there are young people and adults who prefer to improve their living conditions by leaving the original territory of birth and with it their customs and traditions.